2021
DOI: 10.1007/s00401-021-02383-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct characteristics of limbic-predominant age-related TDP-43 encephalopathy in Lewy body disease

Abstract: Limbic-predominant age-related TDP-43 encephalopathy (LATE) is characterized by the accumulation of TAR-DNA-binding protein 43 (TDP-43) aggregates in older adults. LATE coexists with Lewy body disease (LBD) as well as other neuropathological changes including Alzheimer's disease (AD). We aimed to identify the pathological, clinical, and genetic characteristics of LATE in LBD (LATE-LBD) by comparing it with LATE in AD (LATE-AD), LATE with mixed pathology of LBD and AD (LATE-LBD + AD), and LATE alone (Pure LATE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 61 publications
0
40
0
Order By: Relevance
“…TDP-43 proteinopathy was first identified in ALS and frontotemporal lobar degeneration ( Neumann et al, 2006 ). However, TDP-43 neuropathology was also identified in post-mortem AD brain ( Amador-Ortiz et al, 2007 ; Uryu et al, 2008 ; Josephs et al, 2014 , 2016 ), and is often observed in older adults with LATE ( Nelson et al, 2019 ; Katsumata et al, 2020 ; Robinson et al, 2020 ; Uemura et al, 2022 ). TDP-43 frequently coexists with tau and α-synuclein in brain tissue of subjects with AD and dementia with Lewy bodies ( Higashi et al, 2007 ).…”
Section: An Accelerated Historical Perspective Of Alzheimer’s Disease...mentioning
confidence: 99%
“…TDP-43 proteinopathy was first identified in ALS and frontotemporal lobar degeneration ( Neumann et al, 2006 ). However, TDP-43 neuropathology was also identified in post-mortem AD brain ( Amador-Ortiz et al, 2007 ; Uryu et al, 2008 ; Josephs et al, 2014 , 2016 ), and is often observed in older adults with LATE ( Nelson et al, 2019 ; Katsumata et al, 2020 ; Robinson et al, 2020 ; Uemura et al, 2022 ). TDP-43 frequently coexists with tau and α-synuclein in brain tissue of subjects with AD and dementia with Lewy bodies ( Higashi et al, 2007 ).…”
Section: An Accelerated Historical Perspective Of Alzheimer’s Disease...mentioning
confidence: 99%
“…The neuropathologies found in the post-mortem brains of ADRD patients are complex and multifactorial. A number of amyloid isotypes accumulate in the brains of these patients including amyloid-β (Aβ) plaques, neurofibrillary tau tangles (NFTs), Lewy body α-synuclein pathologies, and transactive response DNA and RNA binding protein 43 kDa aggregates ( Nelson et al, 2019 ; Robinson et al, 2021 ; Uemura et al, 2022 ). These neuropathologies are often associated with neurovascular abnormalities including large macroscopic, lacunar and microscopic infarcts, hemorrhages, and vessel pathologies including cerebral amyloid angiopathy, intracranial atherosclerosis and arteriolosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In LBD, the severity of αS pathology in the temporal cortex was observed to be significantly more among TDP-43 positive patients, which correlated with the severity of TDP-43 pathology in the amygdala (26). Perhaps the most compelling evidence for selective influence of αS on TDP-43 proteinopathy comes from LATE patient brains in which distinct neuropathological changes are observed in PrLD/αS aggregates containing LATE-LBD and LATE-AD co-pathologies compared to pure LATE (27).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, incubation of exogenous αS fibrils in SH-SY5Y cells enhances TDP-43 phosphorylation and aggregation (43). More compelling pathological evidence of the interaction between the two proteins comes from a recent study which showed that TDP-43 aggregates co-exist with αS aggregates in LATE-LBD and LATE-AD co-pathologies, exhibiting histopathological differences between pure LATE, LATE-LBD and LATE-AD (27). These observations also suggest that the polymorphic fibrils of TDP-43 observed in these patients could be consequential of the influence by αS.…”
Section: Introductionmentioning
confidence: 99%